Ripening-dependent changes in antioxidant activities and un-targeted phytochemical fingerprinting of mango (Mangifera Indica L.) cultivar Safaid Chonsa - Aniqa; Abdul Mannan; Zarrin Fatima Rizvi (Journal of Nutritional Science)
The ripening-dependent changes in antioxidant activities and phytochemical content of mango (Mangifera indica L.) cultivar Safaid Chonsa at various ripening stages were evaluated. The ripening time period was divided into five stages (RSI-RSV) and the pulp was subjected to proximate analysis, antioxidant potential, and UHPLC/MS-based non-targeted metabolite fingerprinting. Proximate analyses depicted variations in moisture, dry matter, fat, protein, carbohydrate, and energy parameters. Maximum DPPH activity (51%) was observed at stages III, IV, and V while FRSP increased 31% at RS V as compared to stage I. Total antioxidant capacity and total reducing power potential were maximum (295.7 and 345.71 µg AAE/mg extract, respectively at stage V. Total phenolic content increased from 3.57 µg GAE/mg extract to 5.72 µg GAE/mg extract from stage I to RSIII while 19% increase in total flavonoid content was observed at stage V as compared to stage I. UHPLC/MS analysis showed presence of Aconitic acid, methylisocitric acid, 4-O-methyl gallate, beta-glucogallin, xanthenes, sakebiose, Isobergaptene, Fructoselysine 6-phosphate, Citbismine C, and many others at different ripening stages of chonsa mango extracts. The results conclude that during the mango ripening stages, changes in phytochemical composition have positive correlation with antioxidantive potential. These phytochemicals have nutritional and nutraceutical effects on human health therefore ripening stage should be considered for consumption of mango.